A SURVEY ON ENVIRONMENTAL SANITATION AND HYGENE INDICES - K. Imandel; M. Ghiaseddin; M.H. Monshi (Tehran University of Medical Sciences, 1979)
In a thousands beds general hospital affiliated to the Tehran University, long-standing infestations of insects such as cockroaches, flies, mosquitoes and rat were found as a result of vicious circles and substandard clearing which are due to not well trained and drilled personnel of contracting agency, out of work condition of two incinerators, quasti-administrative aspects of their program on hospital sanitation and in controlling of hospital infection. Out of 37 samples collected for bacteriological examination, 21, eases of gram positive cocci and gram negative bacilli were isolated and detected. The intensity of illumination at two operation rooms were substandard level, while the, sound level were exceed the recommended standard.